(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This study examines how structured physical conditioning and tactical game-based training methods affect basketball performance efficiency. Drawing on multivariate training programs and small-sided game (SSG) approaches, the article reviews empirical findings on strength, agility, endurance development, and tactical decision-making. Results suggest that integrated training enhances both physical fitness and game intelligence, leading to improved on-court performance. Practical recommendations outline how coaches can apply these innovations within basketball practice.